Bisphosphonate- and disumab-related gingival disorders: case analysis from the U.S. Food and Drug Administration Adverse Event Reporting System - Lei Wang; Wei Zhang; Cheng-long Zhao; Zhong-hua Fu (Frontiers in Endocrinology, 2024)
Prior research has indicated that bisphosphonates (BPs) can improve periodontal disease because of their anti-osteoporosis properties. In vitro studies have shown that BPs induce cytotoxicity, inhibit wound healing, and thus affect periodontal disease. Denosumab and BPs have alternative indications. BP and denosumab are not known to correlate with gingival disorders. We assessed such a relationship by applying Bayesian and nonproportional analyses to data in the US FDA Adverse Event Reporting System (FAERS) database. The study analyzed BPs and denosumab-reported incidents with preferred terms found in the narrow Standardized MedDRA Queries for gingival disorders. A total of 5863 reported cases of gingival disorders were associated with five BPs (alendronate, pamidronate, ibandronate, risedronate, and zoledronate) and denosumab. More than 15% of patients with gingival disorders related to BPs and denosumab other than denosumab were hospitalized over short- or long-term periods. Our findings indicated BPs and denosumab had significant reporting odds ratios (ROR), proportional reporting ratios (PRR), and information components (IC) with respect to gingival disorders. Pamidronate had the highest association (ROR = 64.58, PRR = 57.99, IC = 5.71), while the weakest association was found with denosumab (ROR = 3.61, PRR = 3.60, IC = 1.77). Significant associations were found between the six drugs and gingival pain, gingival recession, gingivitis, periodontal disease, and periodontitis. In conclusion, our comprehensive overview of the correlations, clinical characteristics, and prognoses of BPs and denosumab-related gingival disorders suggests that these issues deserve continued surveillance and appropriate management.